Human Interventions: Driving Forces of Mosquito Evolution. Issue 2 (February 2018) - Fouet, Caroline; Atkinson, Peter; Kamdem, Colince
Abstract : One of the most common strategies for controlling mosquito-borne diseases relies on the use of chemical pesticides to repel or kill the mosquito vector. Pesticide exposure interferes with several key biological functions in the mosquito and triggers a variety of adaptive responses whose underlying mechanisms are only partially elucidated. The availability of reference genome sequences opens up the possibility of tracking signatures of evolutionary changes, including the most recent, across the genomes of many vector species. In this review, we highlight the recent genomic changes, which contribute to the fascinating adaptation of malaria vectors of the sub-Saharan African region to intensive insecticide-based interventions. We emphasize the operational significance of detailed genomic knowledge for current monitoring and decision-making. Trends: Widespread use of insecticides provides an opportunity to examine the adaptive responses of target species to human interventions. Rapid evolution of anopheline mosquitoes represents a potential threat to any vector-based malaria control effort. The use of high-quality genomic data and gene-editing tools provides powerful strategies for characterizing insecticide resistance genes and their functions in mosquitoes. A better understanding of the genetic, behavioral and physiological mechanisms underlying insecticide resistance will yield potentially vital knowledge for vector-borne disease control.